2016
DOI: 10.3892/ol.2016.5307
|View full text |Cite
|
Sign up to set email alerts
|

Lipid raft localization of epidermal growth factor receptor alters matrix metalloproteinase-1 expression in SiHa cells via the MAPK/ERK signaling pathway

Abstract: Matrix metalloproteinase-1 (MMP-1) has been identified as an important participant in tumor invasion, metastasis and angiogenesis. The purpose of the present study was to investigate the effects of epidermal growth factor receptor (EGFR) localization to lipid rafts on signaling pathways involved in the regulation of MMP-1 expression in SiHa cells, a cervical cancer cell line. EGFR activation by EGF specifically induced MMP-1 expression at both the messenger RNA and protein levels. Additionally, it was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 47 publications
(60 reference statements)
1
30
1
Order By: Relevance
“…1) [10]. Currently, these domains are considered a predominant feature of the plasma membrane and appear to mediate critical signaling processes [11, 12], including the stabilization of β-catenin via stimulation of Wnt pathway-associated receptors [1315], epidermal growth factor receptor (EGFR) signaling [1618], and the activation of MAPK/ERK pathway components through membrane-bound Ras proteins [1921], to name a few examples (Table 1). Interestingly, dysregulation of plasma membrane homeostasis, in part, due to the products of gene mutations as well as changes in protein and lipid localization, alters the degree of clustering and other biochemical and biophysical trademarks, thereby providing a suitable environment for the initiation of cancer-related signaling processes [2224].…”
Section: Introductionmentioning
confidence: 99%
“…1) [10]. Currently, these domains are considered a predominant feature of the plasma membrane and appear to mediate critical signaling processes [11, 12], including the stabilization of β-catenin via stimulation of Wnt pathway-associated receptors [1315], epidermal growth factor receptor (EGFR) signaling [1618], and the activation of MAPK/ERK pathway components through membrane-bound Ras proteins [1921], to name a few examples (Table 1). Interestingly, dysregulation of plasma membrane homeostasis, in part, due to the products of gene mutations as well as changes in protein and lipid localization, alters the degree of clustering and other biochemical and biophysical trademarks, thereby providing a suitable environment for the initiation of cancer-related signaling processes [2224].…”
Section: Introductionmentioning
confidence: 99%
“…EA also binds to GPR40 and 120, inducing the transactivation of EGFR via c-src (5). Lipid rafts represent a special localization of epidermal growth factor receptors (EGFRs), altering its signaling pathways (10) and transactivation (11). Rao et al have reported that EA can affect Fas/FasL-induced apoptosis via lipid rafts (12).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of MMP1 is strongly associated with unfavorable prognosis in multiple malignancies including breast cancer, esophageal squamous cell carcinoma, and ovarian cancer [21][22][23]. MMP1 has also previously been proposed as a risk factor in CC [24,25]. SPP1 participates in the regulation of tumor-associated angiogenesis and in ammation [26].…”
Section: Discussionmentioning
confidence: 99%